2021
DOI: 10.5194/amt-14-6305-2021
|View full text |Cite
|
Sign up to set email alerts
|

ALADIN laser frequency stability and its impact on the Aeolus wind error

Abstract: Abstract. The acquisition of atmospheric wind profiles on a global scale was realized by the launch of the Aeolus satellite, carrying the unique Atmospheric LAser Doppler INstrument (ALADIN), the first Doppler wind lidar in space. One major component of ALADIN is its high-power, ultraviolet (UV) laser transmitter, which is based on an injection-seeded, frequency-tripled Nd:YAG laser and fulfills a set of demanding requirements in terms of pulse energy, pulse length, repetition rate, and spatial and spectral be… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 51 publications
0
25
0
Order By: Relevance
“…This separation between orbital phases is done because of the aforementioned distance to collocation disparities. Nonetheless, several long-term cal/val activities showed significant phase-dependent differences in the determined biases of Aeolus wind measurements (Wu et al, 2021, Iwai et al, 2021Lux et al, 2021;Baars et al, 2020;Rennie and Isaksen, 2020;Geiß et al, 2019; Krisch and the Aeolus DISC, 2020), further assessing the need for an independent study on both cases. The correlation plot of the Aeolus wind is shown in Fig.…”
Section: Statistical Comparison Of Aeolus With Collocated Datamentioning
confidence: 99%
See 1 more Smart Citation
“…This separation between orbital phases is done because of the aforementioned distance to collocation disparities. Nonetheless, several long-term cal/val activities showed significant phase-dependent differences in the determined biases of Aeolus wind measurements (Wu et al, 2021, Iwai et al, 2021Lux et al, 2021;Baars et al, 2020;Rennie and Isaksen, 2020;Geiß et al, 2019; Krisch and the Aeolus DISC, 2020), further assessing the need for an independent study on both cases. The correlation plot of the Aeolus wind is shown in Fig.…”
Section: Statistical Comparison Of Aeolus With Collocated Datamentioning
confidence: 99%
“…To do so, we showed how the distance to collocation had small effects on the bias in Sect.4.2 and how the time difference had a significant impact on the standard deviation in Sect.4.3. Some error sources were pointed out by previous research, e.g., hot pixels and dark current anomalies (Weiler et al, 2021a), Rayleigh wind errors introduced by angular variations (Lux et al, 2022, Lux et al, 2018, Lux et al, 2020a, vibrations introduced by the satellite platform, which affects the Q-switched master oscillator cavity length (Lux et al, 2020b), photon shot noise (Liu et al, 2006), micro-vibrations due to critical rotation speeds of the satellite's reaction wheels (Lux et al, 2021), mechanical disturbances generated by reaction wheels of the class of those embarked on Aeolus (Le., 2017), linear drift in the illumination of the Rayleigh/Mie spectrometers, and the telescope M1 mirror temperature variations Weiler et al, 2021b). In section 4.1, we observe a steep increase in the random error above 25 km, which can be further observed in fig.…”
Section: Rayleigh-clearmentioning
confidence: 99%
“…In this paper, the attention is directed to the receiver side of the system. A more detailed description of ALADIN is given in ESA (2008) and Reitebuch et al (2018); the laser transmitters as well as their frequency stability in space are discussed by Lux et al (2020aLux et al ( , 2021.…”
Section: Instrument Descriptionmentioning
confidence: 99%
“…The two campaigns not only considerably extended the available dataset to validate Aeolus wind observations in different geographical regions and under different atmospheric conditions in terms of cloud types and dynamics, but also served to assess the accuracy and precision of the Aeolus wind product in different phases of the mission. In particular, the switch-over from the first flight model laser (FM-A) to the redundant laser FM-B just after AVATARE in June 2019 marked a caesura, as the FM-B delivered much higher emit energy and hence ensured higher signal-to-noise ratio of the backscatter return compared to the end of the FM-A period (Lux et al 2020b;Lux et al, 2021). Moreover, the satellite instrument was found to be more susceptible to changes in the thermal environment than expected before launch showing orbital and seasonal variations in the beam alignment, and hence in the wind bias (Martin et al, 2021;Chen et al, 2021).…”
Section: Overview Of Validation Campaigns and Datasetsmentioning
confidence: 99%
“…Thanks to these modifications, UV frequency stability of 1.8 MHz and timing stability below 100 ns were simultaneously achieved, thus forming the basis for highly accurate wind measurements. For comparison, the frequency stability of the ALADIN laser is on the order of 8 to 10 MHz (Lux et al, 2021). However, it was found that other error sources limited the accuracy and precision of the A2D wind results.…”
Section: Avatarimentioning
confidence: 99%